2014
DOI: 10.5194/cp-10-51-2014
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Atlantic water variability during the Holocene in the western Barents Sea

Abstract: Abstract. The gravity core JM09-KA11-GC from 345 m water depth on the western Barents Sea margin was investigated for down-core distribution patterns of benthic Foraminifera, stable isotopes, and sedimentological parameters in order to reconstruct the flow of Atlantic water during the Holocene. The core site is located below the Atlantic water masses flowing into the Arctic Ocean and close to the Arctic front. The results show continuous presence of Atlantic water at the margin throughout the Holocene. During … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 61 publications
6
29
1
Order By: Relevance
“…The appearance of the thermophilous mussel Mytilus edulis at the outer part of Woodfjorden (Reinsdyrflya) supports the assumption of a surface injection of AW at least from ∼ 10.6 ka on (9815 ± 80 14 C a; Salvigsen, 2002). Several studies around Spitsbergen report about a benthic faunal pattern comparable to the record above during the HTM (Groot et al, 2014;Rasmussen et al, 2012;Skirbekk et al, 2010;Ślubowska-Woldengen et al, 2007). Ślubowska-Woldengen et al (2008) showed that N. labradorica reached maximum percentages at sites influenced by the WSC or the Svalbard Branch.…”
Section: Early Holocene (∼ 117-78 Ka) -Amelioration Of Environmentasupporting
confidence: 52%
See 2 more Smart Citations
“…The appearance of the thermophilous mussel Mytilus edulis at the outer part of Woodfjorden (Reinsdyrflya) supports the assumption of a surface injection of AW at least from ∼ 10.6 ka on (9815 ± 80 14 C a; Salvigsen, 2002). Several studies around Spitsbergen report about a benthic faunal pattern comparable to the record above during the HTM (Groot et al, 2014;Rasmussen et al, 2012;Skirbekk et al, 2010;Ślubowska-Woldengen et al, 2007). Ślubowska-Woldengen et al (2008) showed that N. labradorica reached maximum percentages at sites influenced by the WSC or the Svalbard Branch.…”
Section: Early Holocene (∼ 117-78 Ka) -Amelioration Of Environmentasupporting
confidence: 52%
“…In contrast to conditions inferred above, some other studies state a general warming trend (Bonnet et al, 2010;D'Andrea et al, 2012;Jernas et al, 2013;Majewski et al, 2009;Spielhagen et al, 2011;Werner et al, 2011) as well as a strengthened influx of AW during the last 2 millennia in the Svalbard area (Groot et al, 2014;Rasmussen et al, 2012;Sarnthein et al, 2003;Ślubowska et al, 2005). However, as the midHolocene is missing in the present record (see Sect.…”
Section: Late Holocene (∼ 18-04 Ka) -Aftermath Of the Neoglaciationcontrasting
confidence: 40%
See 1 more Smart Citation
“…Records of marine sediments from Nordic and Barents Seas (e.g. Rasmussen et al, 2007;Ślubowska-Woldengen et al, 2007Ślubowska-Woldengen et al, , 2008Zamelczyk et al, 2012;Groot et al, 2014) as well as δ 18 O records from Greenland ice cores (e.g. Dansgaard et al, 1993;Grootes et al, 1993;Mayewski et al, 1993;Alley, 2000) show that the YD was characterised by a rapid and short-term temperature decrease.…”
Section: Glacier-proximal Unit (13 450-11 500 Cal Yr Bp)mentioning
confidence: 99%
“…However, the supply of turbid meltwater from land to the study area still resulted in a relatively high sediment accumulation rate. According to Risebrobakken et al (2011) and Groot et al (2014), the presence of Arctic Water suppressed the warming signal in the western Barents Sea. This observation is in agreement with our data on planktonic foraminifera reappearing at the termination of the early Holocene (ca.…”
Section: Glaciomarine Unit I (Early Holocene;mentioning
confidence: 99%